Factors affecting dividend payment policy in Indonesian banking sectors moderated by return on assets - Susilowati, Dwi (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study analyses how the debt-to-equity ratio, current ratio, and free cash flow influence the dividend payment policy moderated by return on assets. Method – This study uses a quantitative approach with secondary data. Every Indonesian bank listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023 as the research population amounts to 47 companies. Observation data of 90 were taken from 18 banks as samples selected using a purposive sampling technique. The data is analyzed using moderated regression analysis (MRA). Based on the results of the Chow and Hausman tests, the random effect model was chosen. Findings – The findings of this study show that the current ratio, free cash flow, and return on assets positively impact the dividend payment policy. In contrast, the debt-to-equity ratio does not impact dividend policy. Return on assets can strengthen the influence of the current ratio and free cash flows on dividend payout. However, return on assets cannot moderate the relationship between debt-to-equity ratio and dividend payout. Implications – This study can complement existing theories and provide a starting point for researchers to investigate dividend theory in the stock market further, advancing the understanding of this complex financial dynamic on a global scale. These findings provide valuable insights for management in setting dividend policy and highlight potential strategies to enhance shareholder value.